Expression and Prognostic Significance of Wnt7a in Human Endometrial Carcinoma. (6th December 2012) - Peng, Chunjie; Zhang, Xiaolei; Wang, Yujie; Li, Lijuan; Wang, Qiuyan; Zheng, Jianhua
Abstract : Introduction . Wnt7a is a secreted glycoprotein that regulates normal cellular proliferation and differentiation as well as tumorigenesis and progression. However, less is understood about the role of Wnt7a in human endometrial carcinoma. The aim of this study is to investigate the expression and prognostic significance of Wnt7a in endometrial carcinoma. Methods . Wnt7a expression was immunohistochemically examined in 35 normal endometrium, 33 hyperplastic endometrium and 70 endometrial carcinomas. Results . Wnt7a expression was lower in endometrial carcinomas compared with that in normal and hyperplastic endometrium (P < 0.001 ). Wnt7a was inversely correlated with FIGO stage (P = 0.001 ), grade (P = 0.001 ), lymph node metastasis (P = 0.002 ), depth of myometrial invasion (P = 0.006 ), lymph vascular space involvement (P = 0.001 ) and peritoneal cytology (P = 0.013 ). There was a negative correlation between estrogen receptor (ER) and Wnt7a (r = − 0.281, P = 0.019 ), and a positive correlation between progestogen receptor (PR) and Wnt7a (r = 0.249, P = 0.037 ). Patients with lost or reduced Wnt7a expression had poorer progression-free survival (PFS) and overall survival (OS) (P = 0.005 and P = 0.042, resp.) on univariate analysis. But on multivariate analysis, Wnt7a expression was not an independent prognostic factor for PFS or OS. Conclusions . Our results indicate that Wnt7a expression may serve as an important prognostic marker.